Neurofilament light chain in psychiatric and neurodegenerative disorders: A 'c‐reactive protein' for the brain?: Biomarkers (non‐neuroimaging) / plasma/serum/urine biomarkers. (7th December 2020) - Eratne, Dhamidhu; Loi, Samantha M.; Santillo, Alexander; Li, Qiao‐Xin; Chadunow, Carolyn; Stehmann, Christiane; Janelidze, Shorena; Malpas, Charles B.; Walia, Nirbaanjot; Varghese, Shiji; Dhiman, Kunal; Lewis, Vicki; et al.
Abstract: Background: Accurate diagnosis of a neurodegenerative disorder, in particular distinguishing primary psychiatric from neurological disorders, can be challenging. There is a need for biomarkers to reduce the diagnostic odyssey and improve outcomes. Neurofilament light (NfL) has shown promise as a biomarker for diagnosis, staging and prognosis in a wide range of disorders. Our 'Biomarkers in Younger Onset Neurocognitive Disorders' (BeYOND) and 'Markers in Neuropsychiatric Disorders' (MiND) studies aim to build on our pilot study (Eratne et al, 2019, ANZJP), to explore the diagnostic and broader utility of plasma and cerebrospinal fluid (CSF) NfL, in a broad range of psychiatric and neurodegenerative/neurological disorders. Method: These studies assess plasma and/or CSF NfL concentrations using Simoa technology in a broad range of cohorts, including: patients assessed for neurocognitive/psychiatric symptoms at Neuropsychiatry and Melbourne Young Onset Dementia service; Australian National Creutzfeldt‐Jakob Disease Registry (ANCJDR); treatment trials in Alzheimer's disease (AD) and frontotemporal dementia (FTD); treatment‐resistant schizophrenia (TRS) biobank; FTD; autoimmune encephalitis; Niemann‐Pick Type C; epilepsy; and patients in primary care with cognitive or psychiatric symptoms. The most recent primary consensus diagnosis informed by established diagnostic criteria is categorised: psychiatric disorder (PSY), neurodegenerative/neurological disorder (NND), or healthy controls (HC). Result: As of January 2020, data from 485 patients/participants (NND:325, PSY:100, HC:60) demonstrates significantly elevated plasma and/or CSF NfL levels in a broad range of NND compared to a broad range of PSY, and HC, with areas under the curve of>0.90 and sensitivity and specificity>90%: improving on results from our pilot study. As recruitment, sample analysis, data collection is ongoing, more detailed, up to date results will be presented from over 600 patients/participants, including in‐depth findings from TRS, ANCJDR, AD and FTD treatment trials, and general practice cohorts. Conclusion: NfL shows great promise as a diagnostic test to assist with the common, but challenging diagnostic dilemma of distinguishing psychiatric from neurodegenerative and neurological disorders. A significantly elevated NfL concentration in a patient with a psychiatric diagnosis should prompt consideration of neurological or neurodegenerative differentials. Plasma NfL could dramatically alter clinical care of patients with neurological/neurodegenerative and psychiatric disorders, improving outcomes for patients, their families, the healthcare system, and clinical trials.